Stanovanjski status in osamosvajanje mladih v Mestni občini Ljubljana - Kuhar, Metka (Družboslovne razprave, 2018)
The article presents research results concerning young adults who leave home in the Municipality of Ljubljana. By considering already known patterns of young adults' prolonged co-residence with their parents, the article aims to find out whether data on young adults from the Ljubljana municipality (2017) confirm what is already known or reveal changes or specific aspects. The results show: 1. a consistent picture of prolonged living in the family of origin (with gender, intimate partnership, employment as the main predictors); 2. paternal financial support even for young people who have left the parental home; and 3. a diverse and dynamic period of various living arrangements ranging between fully living in the family of origin and having one's own full residential independence. The results point to a new characteristic of a greater share of young people living in privately rented apartments, which may be specific to the Ljubljana municipality.
Keywords: Družina; Emancipation; Family; Housing; Mladi odrasli; Osamosvojitev; Stanovanje; Young adults